The impact of capillary structure properties on heat transfer from boiling in limited space - Баскова, Александра Александровна; Кравец, Владимир Юрьевич; Алексеик, Ольга Сергеевна; Лебедь, Наталия Леонидовна (Eastern-European Journal of Enterprise Technologies, 2015)
Modern cooling systems for radio and electronic equipment widely use heat pipes. The main element of heat pipes is capillary and porous structure (CPS), on which a heat transfer agent boils and condensates. Previous studies showed that intensity of heat transfer depends on geometric parameters of the CPS. Our research is devoted to analyzing experimental data on the intensity of heat transfer from boiling in limited space on the CPS with various fiber lengths. We have determined the impact of space limit on boiling intensity on the CPS. The analysis of the findings has proved that within limited space, when the height of the volume limiter is 5 to 16 mm above the working surface and the density of the heat flow rises to 200 kW/m2, the intensity of heat transfer increases. A comparison of boiling intensity on CPSs in large space with boiling intensity in limited space has shown that at the fiber length of 5 mm heat transfer coefficients are similar. Further fiber lengthening leads to decrease in heat transfer intensity.